The Utilization of Interactive Digital Media to Increase Learning Interest of Elementary School Students in Merdeka Curriculum Era - Afni Firdausia; Maulida Fikria Nasol (Al Hikmah: Journal of Education, 2025)
This study aims to examine the effectiveness of interactive digital media on student learning interest, the suitability of interactive digital media with the principles of differentiated learning in the Merdeka Curriculum, and the obstacles to implementation and its implications in learning practices in elementary schools. This study is a systematic review, conducted by comparing and analyzing articles retrieved from the Google Scholar digital database using the Publish and Perish application. Articles were searched using predetermined keywords, then excluded according to set parameters, resulting in eight reference articles. The results of the study indicate that the various uses of digital learning media in differentiated learning can increase student interest, participation, independence, and understanding; there is a need for interactive digital media to be appropriate in terms of selection and design, taking into account the characteristics of elementary school levels. However, the effectiveness of interactive digital media implementation still faces obstacles such as infrastructure limitations, limited digital skills of teachers, internet access gaps, student ability to use the digital media, and media is not aligned with learning objectives. This study recommends increasing teacher capacity and providing supporting facilities and collaborative efforts from various parties, including teachers, schools, and so that the use of interactive digital media is more optimal.